Pemodelan Kasus Pneumonia pada Balita di Indonesia Menggunakan Geographically Weighted Negative Binomial Regression - Zulvatul Hasanah; Ni Luh Putu Suciptawati; Ida Ayu Putu Ari Utari (Journal on Education, 2024)
Pneumonia is one of the infectious diseases resulting in significant mortality rates among children under the age of five in Indonesia. In 2020, East Java recorded the most significant incidence of pneumonia among children under the age of five, with a total of 76,929 cases. Modelling pneumonia cases might be employed to ascertain the factors affecting it. The pneumonia case data in Indonesia exhibits overdispersion, indicating that the appropriate model to utilize is Negative Binomial regression. This study employed the Geographically Weighted Negative Binomial Regression (GWNBR) model to analyze the distribution of pneumonia cases among children in Indonesia, which exhibited different characteristics and data variety. The modelling results indicated that using adaptive bisquare kernel weighting identified five different groups. These groups were determined based on the predictor variables that significantly affected the number of pneumonia cases among children under the age of five in Indonesia.